2004
DOI: 10.1289/ehp.7051
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Occupational Exposure to 2,3,7,8-Tetrachlorodibenzo- p -dioxin and Birth Outcomes of Offspring: Birth Weight, Preterm Delivery, and Birth Defects

Abstract: Agent Orange is a phenoxy herbicide that was contaminated with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). We studied pregnancy outcomes among wives of male chemical workers who were highly exposed to chemicals contaminated with TCDD and among wives of nonexposed neighborhood referents. For exposed pregnancies, we estimated serum TCDD concentration at the time of conception using a pharmacokinetic model. The mean TCDD concentration for workers’ births was 254 pg/g lipid (range, 3–16,340 pg/g). The mean referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 31 publications
(46 reference statements)
0
16
1
1
Order By: Relevance
“…Although to date these studies have failed to identify a significant increase in risk of PTB correlating to TCDD exposure, a non-significant increase in risk was noted in the most heavily exposed individuals [47,48]. With regard to paternal exposure, at least two studies have examined birth outcomes in women whose partners were exposed to TCDD via the herbicide known as Agent Orange [49,50]. As with the Seveso cohort, neither of these studies revealed a significant increase in PTB in the wives of men occupationally exposed to TCDD [49,50]; however, these studies examined the impact of an adult exposure on subsequent pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although to date these studies have failed to identify a significant increase in risk of PTB correlating to TCDD exposure, a non-significant increase in risk was noted in the most heavily exposed individuals [47,48]. With regard to paternal exposure, at least two studies have examined birth outcomes in women whose partners were exposed to TCDD via the herbicide known as Agent Orange [49,50]. As with the Seveso cohort, neither of these studies revealed a significant increase in PTB in the wives of men occupationally exposed to TCDD [49,50]; however, these studies examined the impact of an adult exposure on subsequent pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Dioxin and other organochlorine chemicals have been shown to interfere with male and female reproductive development in experimental and wild animals, particularly during gestational exposure (Gao et al, 1999;Grey and Ostby, 1995;Roman et al, 1998;Sonne et al, 2006;Theobald et al, 1997). In studies of women with environmental or accidental exposures, associations between dioxin-like chemical exposures and various reproductive endpoints (Eskenazi et al, 2003;Lawson et al, 2004;Schnorr et al, 2001;Warner et al, 2004 and and endometriosis (Eskenazi et al, 2002;Fierens et al, 2003;Heilier et al, 2005;Hoffman et al, 2007) have been either absent or of unknown significance, though animal studies have demonstrated reproductive effects at high doses (Arisawa et al, 2005;U.S. EPA, 2004).…”
Section: Dioxin-like Chemicalsmentioning
confidence: 99%
“…At first, the results of Mocarelli et al (2000) seemed to confirm the prediction (as did those of and Del Rio Gomez et al (2002)). But other workers (Schnorr et al, 2001;Karmaus et al, 2002;Lawson et al, 2004) reported failures to confirm, perhaps as a result of contamination with androgenic or estrogenic congeners . (Mocarelli et al (2000) emphasized that the dioxin to which their subjects had been exposed in Seveso was pure).…”
Section: Article In Pressmentioning
confidence: 99%